Sincerity in corporate philanthropy, stakeholder perceptions and firm value - CUYPERS, Ilya R. P. (Institutional Knowledge at Singapore Management University, 2016)
This study extends the literature on symbolic management by incorporating the role of stakeholder perceptions into the context of corporate philanthropy. In particular, we differentiate between the quantitative (generous giving) and qualitative (innovative giving) aspects of giving. We argue that although stakeholders may perceive both types of giving as being substantive rather than symbolic, innovative giving is likely to be perceived as more substantive than generous giving is and, thus, has a greater impact on firm value. Furthermore, stakeholder perceptions of corporate philanthropy as being more symbolic or substantive are influenced by firm characteristics—the type of products or services that a firm provides and the life-cycle stage that the firm is in—which provide stakeholders with a context to better assess the nature of a firm’s philanthropic actions and the substantiveness of its giving. We find support for our predictions using a sample covering U.S. firms’ philanthropic activities over a 19-year period.